Application of acoustic impedance gun to non-destructively monitor stone damage. (14th March 2022) - Navacerrada, M.A.; Barbero-Barrera, M.M.; Fort, R.; de la Prida, D.; Núñez, J.C.; Gómez, T.S.
Highlights: Impedance gun was used to non-destructively evaluate stone damage. Ashlar and stone slab damages were measured in situ and in laboratory, respectively. This technique supports detection of lesions on stone surfaces. Technique is very easy to use and quickly measures large areas. Damage assessment measurements must be conducted close to stone surfaces. Abstract: Conserving historical heritage sites is fundamental for preserving cultural identity. Effective interventions require building damage to be pre-detected. Because stone masonry is one of the most globally prevalent building techniques, diagnosing building deterioration is pivotal for conserving heritage sites. Non-destructive tests (NDTs) provide necessary conservation information and characterise original materials and building techniques without damaging buildings. Recently, NDTs including infrared thermography imaging, p -wave velocity, and electrical resistivity tomography have developed and evaluated for assessing building deterioration. This research investigated the application of a pressure/particle-velocity impedance gun as an NDT to detect building damage. The impedance gun supports the detection of lesions on stone surfaces according to variations in the sound absorption coefficient. Although commonly applied to acoustical measurements, the impedance gun could also be useful to detect stone alterations including ( inter alia ) flaking, alveolisation, rounding, fissuring, and efflorescence damage. Impedance gun measurements in the laboratory and in situ are discussed for both in-situ sound absorption and Scan and Paint operating modes wherein the stone surface scanning was filmed. Surface edges or lesions exhibiting material loss appeared as areas exhibiting the maximum sound absorption in the images. Dirt or salt layers, which altered the stone surface porosity, varied sound absorption coefficients more than the baseline coefficients of pathology-free stones. The impedance gun measured large areas rapidly and easily under various non-extreme environmental conditions and did not interfere with building functioning. In - situ measurements with some non-destructive techniques involve setting up a grid system on |building stones and determining the measurement points. Therefore, the impedance gun can be used to initially assess building surface conditions and identify which areas should be studied in more detail. The research findings suggested that the impedance gun could be applied as a complementary NDT for evaluating damage to cultural heritage sites.